Calculation and research itinerary fuel consumption of a car by its acceleration on the designated distance - Savenkov, Nikita (Univerzita Pardubice, 2010)
I have worked out a computing method of itinerary fuel consumption of a car by its acceleration on the designated distance. In the process of acceleration an engine spends a considerable part of power for overcoming of inertial force and itinerary resistance. At the same time the fuel consumption increases substantially, if an engine behavior is not refined and not agreed with parameters of transmission. The solving of this question is especially actual in connection with a leap of intensity of transport streams, like in cities and on country roads, what sets conditions for an increase number of cycles of acceleration and deceleration of a vehicle. The suggested strategy permits to make a right choice of mechanical advantages at a designated earlier number of transmissions and appropriate to these transmissions load factor of an engine. It gives a possibility to recommend the results of analysis for design of a car transmission, in particular gearbox, like mechanical and automatic. The use of hydromechanical gearboxes and automatic transaxle (CVT type) joint with electronic systems of their control will supply the rise of an average effective coefficient of efficiency of an engine in the process of acceleration of an engine of a car оn the basis of increase of an overall performance of transmission and will result in reduction of itinerary fuel consumption.
Keywords: itinerary fuel consumption of a car; accelerations; load factor of an engine